Five new ways to use nursing research at the point-of-care: tips for fast search, specific and highly relevant - Cruz, Isabel CF da (Online Brazilian Journal of Nursing, 2010)
HTML clipboard It is imperative to develop skills to integrate research and patient care for nurses through the access to the research findings at internet databases.